Effect of Supplementation of Monomix and/or Pharmacological Levels of Zinc Oxide on Growth Performance of Nursery Pigs - K. L. Batson; L. L. Thomas; J. C. Woodworth; M. D. Tokach; R. D. Goodband; S. S. Dritz; J. M. DeRouchey; J. Bryte (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 354 pigs (DNA; 200 × 400; initial BW = 13.0 lb) were used in a 35-d growth trial to evaluate the effects of a short and medium chain fatty acid product (Monomix, Quality Technology International, Inc., Elgin, IL) added alone or in combination with pharmacological levels of ZnO on nursery pig performance. Upon arrival to the nursery research facility, pigs were randomly assigned to pens (5 pigs per pen) and pens were allotted to 1 of 4 dietary treatments with 18 pens per treatment. Dietary treatments were arranged in a 2 × 2 factorial with main effects of added ZnO (0 vs. 3,000 ppm/2,000 ppm in phases 1 and 2, respectively) and Monomix (0 vs. 0.4% in phases 1, 2, and 3). Treatment diets were formulated in three dietary phases fed from d 0 to 7, 7 to 18, and 18 to 35 post-weaning and were formulated to be isocaloric. No ZnO × Monomix interactions (P= 0.399) were observed throughout the 35-d study. There was no evidence for differences for the pigs consuming diets with added Monomix, other than decreased feed intake (P= 0.002) and average daily gain (ADG;P= 0.012) from d 0 to 7, resulting in decreased body weight (BW) (P= 0.015) at d 7. From d 0 to 7 and 7 to 18, pigs fed diets with added ZnO had increased ADG (P<0.001), average daily feed intake (ADFI), and BW, and improved feed efficiency (F/G). Overall from d 0 to 35, pigs fed diets with added ZnO in phases 1 and 2 had increased (P<0.05) ADG, ADFI, and d 35 BW, with no evidence for differences in performance in pigs fed diets with Monomix. In summary, the addition of Monomix did not improve pig performance, whereas pharmacological levels of ZnO improved ADG and ADFI similarly to previous studies.
Keywords: nursery pig; short chain fatty acids; medium chain fatty acids; zinc oxide